CX3CR1-CCR2-dependent monocyte-microglial signaling modulates neurovascular leakage and acute injury in a mouse model of childhood stroke. Issue 10 (October 2019) - Faustino, Joel; Chip, Sophorn; Derugin, Nikita; Jullienne, Amandine; Hamer, Mary; Haddad, Elizabeth; Butovsky, Oleg; Obenaus, Andre; Vexler, Zinaida S
Stroke is among the top 10 causes of death in children. The developmental stage of the brain is central to stroke pathophysiology. The incidence of childhood arterial ischemic stroke (CAIS) is lower than of perinatal arterial ischemic stroke but the rate of recurrence is strikingly high. Vascular inflammation is seen as major contributor to CAIS but the mechanisms that govern structural-functional basis of vascular abnormalities remain poorly understood. To identify the contribution of immune-neurovascular interactions to CAIS, we established stroke model in postnatal day 21 (P21) mice. We demonstrate acute functional deficits and histological injury and chronic MRI-identifiable injury, brain atrophy and marked derangements in the vascular network. In contrast to negligible albumin leakage and neutrophil infiltration following acute perinatal stroke, CAIS leads to significantly increased albumin leakage and neutrophil infiltration in injured regions of wild type mice and mice with functional CX3CR1-CCR2 receptors. In mice with dysfunctional CX3CR1-CCR2 signaling, extravascular albumin leakage is significantly attenuated, infiltration of injurious Ccr2 + -monocytes essentially aborted, accumulation of Ly6G+ neutrophils reduced and acute injury attenuated. Unique identifiers of microglia and monocytes revealed phenotypic changes in each cell subtype of the monocyte lineage after CAIS. Taken together, CX3CR1-CCR2-dependent microglia-monocyte signaling contributes to cerebrovascular leakage, inflammation and CAIS injury.